1975
DOI: 10.1111/j.1095-8649.1975.tb04592.x
|View full text |Cite
|
Sign up to set email alerts
|

Some blood parameters of the rainbow trout (Salmo gairdneri Richardson)

Abstract: Some of the blood constituents of male, female and immature rainbow trout of the Shasta variety, maintained in known environmental and dietetic conditions, were examined and the results statistically treated. The parameters for male and female trout were similar, only the erythrocyte count exhibiting a significant difference. Large but expected differences were evident between the parameters for mature and immature fish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
15
1
1

Year Published

1977
1977
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 2 publications
9
15
1
1
Order By: Relevance
“…The Hct and Lct values of this study agree with those found in other research on fish blood (Hattingh, 1972, McCarthy et al, 1973and 1975, Schippers et al, 1994. The relative abundance of the different peripheral blood cells showed a predominance of old lymphocytes which is consistent with that reported for other species (Boon et al, 1990b, Peutz et al, 1996, Schippers et al, 1994.…”
Section: Discussion Discussion Discussionsupporting
confidence: 92%
“…The Hct and Lct values of this study agree with those found in other research on fish blood (Hattingh, 1972, McCarthy et al, 1973and 1975, Schippers et al, 1994. The relative abundance of the different peripheral blood cells showed a predominance of old lymphocytes which is consistent with that reported for other species (Boon et al, 1990b, Peutz et al, 1996, Schippers et al, 1994.…”
Section: Discussion Discussion Discussionsupporting
confidence: 92%
“…Lymphocytopenia and neutrophilia were shown to occur in relationship to the spawning period (McCarthy et al, 1975;Ranzani-Paiva & Godinho, 1983;Kavamoto et al, 1985;Pickering, 1986) or stress due to low water temperature (Bennet & Neville, 1975;Pickering, 1986). Similar changes can occur due to parasitic infections.…”
Section: Discussionmentioning
confidence: 84%
“…The sedimentation rate of erythrocytes of rainbow trout has been reported by Barnhart (1969) and McCarthy, Stevenson & Roberts (1973, 1975). An increase in rate was observed in brook trout with furunculosis infection (Schumacher, Hamilton & Longtin, 1956).…”
Section: Erythrocyte Sedimentation Ratementioning
confidence: 84%